Tocqueville on poverty in industrial democracies (2011)
In this paper I explore Tocqueville's views on poverty and pauperism in democratic times. Tocqueville's explanation of economic and social phenomena linked to the raise of equality, show the difficult dilemmas he foresaw with the consolidation of democracy and increasing industrialization. New social classes and the unequal access to wealth would generate a social problem which could, eventually, threaten freedom.